Beneficial Effect of Bupleurum Polysaccharides on Autoimmune-Prone MRL-lpr Mice - Yi-Wen Jiang; Hong Li; Yun-Yi Zhang; Wen Li; Yi-Fan Jiang; Ying-Ye Ou; Dao-Feng Chen (Clinical and Developmental Immunology, 2012)
Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease leading to inflammatory tissue damage in multiple organs. The crude polysaccharides (BPs) isolated from the roots of Bupleurum smithii var. parvifolium have anticomplementary activity and immunomodulatory functions on macrophages. To study its potential benefit on SLE, we examined effects of BPs on MRL-lpr mice, which have similar disease features to human SLE. MRL-lpr mice were treated orally with BPs 15, 30, or 60 mg kg−1 day−1 for 12 weeks and their SLE characteristics were evaluated. The results revealed that BPs elongated life span, improved kidney function, delayed lymphadenopathy, and reduced autoantibodies. It seemed to be mediated by inhibition of complement and macrophages activation and suppression of interferon-γ (IFN-γ) and interleukin-6 (IL-6) gene expression in the kidney. These results implicate that BPs may be an immunomodulator for the treatment of autoimmune diseases like SLE.